Challenge Feeding and Milk Production Performance in Crossbred Cows - Kamboj, M.L.; Mengistu, R.A.; Bindal, S.; Datt, Chander (Indian Journal of Animal Nutrition, 2018)
Ten advanced pregnant crossbred (Karan Fries) cows were randomly allotted to 2 groups of 5 each to evaluate the effect of ‘challenge feeding’ on performance and economics of milk production. The animals in control group were given standard ration while in challenge fed (treatment) group, the animals were givenadditional amount of concentrate mixture. The mean DMI of cows during prepartum period was similar (2.44±0.05 and 2.62±0.06 kg/100 kg BW) in both groups. However, the postpartum DMI was higher (P